Analisis Yuridis Penerapan Pasal 49 Kitab Undang – Undang Hukum Pidana Tentang Pembelaan Terpaksa Terhadap Tindak Pidana Kekerasan Seksual Dalam Putusan Nomor: 09/Pid.B/2013/PTR - Gracela, Naomi; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In everyday life there are many conflicts or problems, even leading to criminal acts. So in the prevention of criminal acts, the Republic of Indonesia established a regulation that contains legal sanctions against the perpetrators contained in Law Number 1 Year 1946 concerning the Criminal Code (hereinafter referred to as KUHP).In the Criminal Code, in the first book of Chapter III there are articles that regulate matters that abolish the punishment of a defendant. If a defendant gets things or circumstances that are stipulated in the articles of the Criminal Code concerned, those things or conditions are the reasons for releasing the defendant from punishment, one of which is an act taken by someone in protecting himself or another person from being punished. an emergency threat.This type of research can be classified as normative, this research is a study of legal principles related to juridical analysis of the application of article 49 of the criminal code on forced defense against criminal acts of sexual violence in decision number: 09/Pid.B/2013/PTR. Data sources are supported by secondary data sources which consist of 3 legal materials, namely: primary legal materials, secondary legal materials, tertiary legal materials. The data collection technique is literature review.From the research results it can be concluded that the application of article 49 of the criminal code on forced defense in criminal acts of sexual violence did not work properly.Keywords: Application of Article 49 of the Criminal Code - Forced Defense - Crime of Sexual Violence